Mengoptimalkan Pembelajaran Apresiasi Puisi Melalui Pemanfaatan Media Sosial pada Mahasiswa di Universitas Peradaban - IRMA, CINTYA NURIKA; BAGIYA, BAGIYA; YUDMIANTI, SITI VITANDARI (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
The purpose of this study was to describe and explain (1) optimization of poetry appreciation learning for Indonesian Language Education students at the Peradaban University through the use of social media and (2) students' interest in learning after using social media in learning poetry appreciation. The method in this research is a case study. The focus of research is related to learning poetry with supporting data for interviews and documentation.Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results showed that (1) social media becomes a medium that can improve students' language skills and critical thinking as an actualization of poetry appreciation learning which includes introduction, recitation, and poetry production through the use of YouTube, Facebook, Instagram, and the Website, (2) the use of media social in learning poetry has an effect on improving cognitive, affective, and psychomotor aspects. The cognitive aspect leads to the stages of understanding and the thought process of introducing, studying, and producing poetry. Affective aspects related to the process of inspiration, organization, assessment, and attitude.